2002
DOI: 10.1093/toxsci/69.1.183
|View full text |Cite
|
Sign up to set email alerts
|

HSP90alpha, HSP90beta, and p53 Expression following in Vitro Hyperthermia Exposure in Gestation Day 10 Rat Embryos

Abstract: The studies presented here are aimed at understanding the expression of p53, HSP90alpha, and HSP90beta in gestation day (GD) 10 CD rat embryos. GD 10 rat embryos were exposed in vitro to 37 degrees C or 42 degrees C for 15 min, then cultured at 37 degrees C for 0.5, 1, 3, or 5 h. Immunohistochemistry was performed on formalin-fixed, paraffin embedded, sectioned embryos for p53, HSP90alpha, or HSP90beta expression. p53 expression was minimal in control embryos but was induced with heat exposure. Maximum express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…There has not been consistent demonstration of p53 expression in the embryonic heart. There is no immunohistochemical detection of p53 protein in hearts of gd10 rat embryos exposed to normal or hyperthermic conditions in vitro, despite its induction in developing brain, eye, and somites (Dugyala et al, 2002). Chemically induced genotoxic stress in gd8 mouse embryos likewise induces p53 gene expression and apoptosis in neural tissues but not heart (Wubah et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has not been consistent demonstration of p53 expression in the embryonic heart. There is no immunohistochemical detection of p53 protein in hearts of gd10 rat embryos exposed to normal or hyperthermic conditions in vitro, despite its induction in developing brain, eye, and somites (Dugyala et al, 2002). Chemically induced genotoxic stress in gd8 mouse embryos likewise induces p53 gene expression and apoptosis in neural tissues but not heart (Wubah et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of p53 has not been consistently demonstrated in the developing heart. No p53 expression was found in hearts of gestation day (gd)10 rat or gd8 mouse embryos under normal or stressed conditions (Wubah et al, 1996; Dugyala et al, 2002). However, p53 expression was demonstrated in the hearts of chick, rat, and human embryos (Miosge et al, 1997; Lichnovsky et al, 1998; Rees et al 1999; Krinka et al, 2001) and in response to hypoxia in chick cardiomyocytes (Chandel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, accumulation of glycogen and lipid was observed on histology, suggesting that CYP4A1 gene expression was in some part induced by the change in lipid metabolism. Heat shock induces HSP90 and p53 gene expression, 22,23 and cold stress upregulates Cirp and p53 gene expression 24,25 . As to cold response, HSP90 gene expression is not induced during cold stress itself but is induced on rewarming after cold treatment 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Both p53‐dependent and ‐independent mechanisms have been evoked in the induction of apoptosis by hyperthermia [Abe et al, 2001; Dugyala et al, 2002; Guan et al, 2002; Mikheeva et al, 2004; Yasumoto et al, 2003, 2004; Nashimoto et al, 2005]. The mediation of apoptosis by p53 frequently involves activation down stream of Bax [Tamamoto et al, 2003].…”
Section: Discussionmentioning
confidence: 99%